Sonothrombolysis: experimental evidence - Daffertshofer, Michael; Hennerici, Michael G. (Handbook on neurovascular ultrasound, 2006)
Reopening of the occluded artery is the primary therapeutic goal in hyperacute ischemic stroke. Systemic treatment with tissue recombinant plasminogen activator (tPA) has been shown to be beneficial at least in a 3-hour door to needle window. Intra-arterial thrombolysis is favorable and opens the window of treatment up to at least 6 h but consequences invasive intra-arterial angiography in a high number of patients, of whom a significant number do not finally receive thrombolysis. The combination of ultrasound with thrombolytic agents may enhance the potential benefit by means of enzyme-mediated thrombolysis. When ultrasound is applied externally through skin or chest, attenuation will be very low. Attenuation, however, is significantly higher if penetration through the skull is required. Attenuation is frequency dependent, with ultrasound intensity being <10% of the output intensity for diagnostic frequencies (>1 MHz). This ratio nearly reverses in the kiloHertz range (>500 kHz). Ultrasound insonation is efficient for accelerating enzymatic thrombolysis within a wide range of intensities, from 0.5W/cm2 (MI approximately 0.3) to several watts per square centimeter, particularly in the nonfocused ultrasound field. Insonation with ultrasound increased tPA-mediated thrombolysis up to 20% in a static model, while it enhanced the recanalization rate from 30 to 90% in a flow model. Results from embolic rat models suggest that low-frequency ultrasound with 0.6W/cm2 significantly reduces infarct volume compared to pure tPA treatment. Safety of ultrasound exposure of the brain for therapeutic purposes has to address hemorrhage, heating, and direct tissue damage. Since animal studies suggested no increase of bleeding rate or harm to the blood-brain barrier, a clinical phase II study applying low-frequency ultrasound at approximately 300 kHz found a high number of secondary hemorrhages. Heating depends critically on the characteristics of the ultrasound. The most significant heating of the brain tissue itself is >1 degrees C per hour using a 2W/cm2 probe; however, no significant heating could be found when using an emission protocol pulsing the ultrasound. The current experimental data helps to identify the optimal ultrasound characteristics for sonothrombolysis and supports the hypothesis combined treatment being a perspective in optimizing thrombolytic therapy in acute stroke.
Gesehen am 05.05.2022